Determining the 3D orientation of optically trapped upconverting nanorods by in situ single-particle polarized spectroscopy. Issue 1 (26th November 2015) - Rodríguez-Sevilla, Paloma; Labrador-Páez, Lucía; Wawrzyńczyk, Dominika; Nyk, Marcin; Samoć, Marek; Kar, Ajoy Kumar; Mackenzie, Mark D.; Paterson, Lynn; Jaque, Daniel; Haro-González, Patricia
Abstract : Single-particle polarized spectroscopy reveals the spatial orientation of single NaYF4 :Er 3+, Yb 3+ upconverting nanorods inside single- and multiple-beam optical tweezers. Abstract : An approach to unequivocally determine the three-dimensional orientation of optically manipulated NaYF4 :Er 3+, Yb 3+ upconverting nanorods (UCNRs) is demonstrated. Long-term immobilization of individual UCNRs inside single and multiple resonant optical traps allow for stable single UCNR spectroscopy studies. Based on the strong polarization dependent upconverted luminescence of UCNRs it is possible to unequivocally determine, in real time, their three-dimensional orientation when optically trapped. In single-beam traps, polarized single particle spectroscopy has concluded that UCNRs orientate parallel to the propagation axis of the trapping beam. On the other hand, when multiple-beam optical tweezers are used, single particle polarization spectroscopy demonstrated how full spatial control over UCNR orientation can be achieved by changing the trap-to-trap distance as well as the relative orientation between optical traps. All these results show the possibility of real time three-dimensional manipulation and tracking of anisotropic nanoparticles with wide potential application in modern nanobiophotonics.